Characterisation of HBV and co-infection with HDV and HIV through spatial transcriptomics - Upkar S Gill; Patrick T F Kennedy; Andrew Hall; Rageshri Dhairyawan; Alberto Quaglia; James M Harris; Colin Nixon; Fadi Issa; Amy Cross; Edward Arbe-Barnes; Jane A McKeating; Dimitra Peppa (eGastroenterology)
Background and aims The intrahepatic processes associated with chronic hepatitis B (CHB), especially in the context of hepatitis delta virus (HDV) and HIV co-infection, require a better understanding. Spatial transcriptomics can provide new insights into the complex intrahepatic biological processes, guiding new personalised treatments. Our aim is to evaluate this method characterising the intrahepatic transcriptional landscape, cellular composition and biological pathways in liver biopsy samples from patients with hepatitis B virus (HBV) and HDV or HIV co-infection.Method The NanoString GeoMx digital spatial profiling platform was employed to assess expression of HBV surface antigen and CD45 in formalin-fixed paraffin-embedded (FFPE) biopsies from three treatment-naïve patients with chronic HBV and HDV or HIV co-infection. The GeoMx Human Whole Transcriptome Atlas assay quantified the expression of genes enriched in specific regions of interest (ROIs). Cell type proportions within ROIs were deconvoluted using a training matrix from the human liver cell atlas. A weighted gene correlation network analysis evaluated transcriptomic signatures across sampled regions.Results Spatially discrete transcriptomic signatures and distinct biological pathways were associated with HBV infection/disease status and immune responses. Shared features including ‘cytotoxicity’ and ‘B cell receptor signalling’ were consistent across patients, suggesting common elements alongside individual traits. HDV/HBV co-infection exhibited upregulated genes linked to apoptosis and immune cell recruitment, whereas HIV/HBV co-infection featured genes related to interferon response regulation. Varied cellular characteristics and immune cell populations, with an abundance of γδT cells in the HDV/HBV sample, were observed within analysed regions. Transcriptional differences in hepatocyte function suggest disrupted metabolic processes in HDV/HBV co-infection potentially impacting disease progression.Conclusion This proof-of-principle study shows the value of this platform in investigating the complex immune landscape, highlighting relevant host pathways to disease pathogenesis.